Emerging powers in their regions: China's impact on its neighbours' political systems - Julia Bader (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Driven mainly by domestic imperatives, China has emerged as a new economic and political player in its region. This rise coincides with a tendency towards autocratisation in Asia that has been facilitated to some extent by a convergence of the interests of China's and its neighbours' governments. Faced with this reality, the West should reflect on its strategies for the further enhancement of human development: it should integrate China into the donor architecture, help it to improve its domestic governance and pursue a more principled engagement in Asian developing countries.
Keywords: 330